Potassium supply and homeostasis in the osmotolerant non-conventional yeasts Zygosaccharomyces rouxii differ from Saccharomyces cerevisiae - Stříbný, Jiří; Kinclová-Zimmermannová, Olga; Sychrová, Hana (Current genetics, 2012)
Three different transport systems exist to accumulate a sufficient amount of potassium cations in yeasts. The most common of these are Trk-type transporters, which are used by all yeast species. Though most yeast species employ two different types of transporters, we only identified one gene encoding a potassium uptake system (Trk-type) in the genome of the highly osmotolerant yeast Zygosaccharomyces rouxii, and our results showed that ZrTrk1 is its major (and probably only) specific potassium uptake system. When expressed in Saccharomyces cerevisiae, the product of the ZrTRK1 gene is localized to the plasma membrane and its presence efficiently complements the phenotypes of S. cerevisiae trk1∆ trk2∆ cells. Deletion of the ZrTRK1 gene resulted in Z. rouxii cells being almost incapable of growth at low K(+) concentrations and it changed some cell physiological parameters in a way that differs from S. cerevisiae. In contrast to S. cerevisiae, Z. rouxii cells without the TRK1 gene contained less potassium than the control cells and their plasma membrane was significantly hyperpolarized compared with those of the parental strain when grown in the presence of 100 mM KCl. On the other hand, subsequent potassium starvation led to a substantial depolarization which is again different from S. cerevisiae. Plasma-membrane hyperpolarization did not prevent the efflux of potassium from Z. rouxii trk1Δ cells during potassium starvation, and the activity of ZrPma1 is less affected by the absence of ZrTRK1 than in S. cerevisiae. The use of a newly constructed Z. rouxii-specific plasmid for the expression of pHluorin showed that the intracellular pH of the Z. rouxii wild type and the trk1∆ mutant is not significantly different. Together with the fact that Z. rouxii cells contain a significantly lower amount of intracellular potassium than identically grown S. cerevisiae cells, our results suggest that this highly osmotolerant yeast species maintain its intracellular pH and potassium homeostasis in way(s) partially distinct from S. cerevisiae.
Keywords: proteiny přenášející kationty; biologický transport; sekvenční homologie; Cation Transport Proteins; membránové potenciály; homologní rekombinace; Membrane Potentials; buněčná membrána; geny hub; Zygosaccharomyces; draslík; DNA fungální; Homeostasis; regulace genové exprese u hub; delece genu; Homologous Recombination; Potassium; koncentrace vodíkových iontů; Saccharomyces cerevisiae; Genes, Fungal; Cell Membrane; Sequence Alignment; Adaptation, Biological; Biological Transport; Gene Deletion; sekvence aminokyselin; Gene Expression Regulation, Fungal; sekvenční seřazení; Saccharomyces cerevisiae Proteins; Amino Acid Sequence; DNA, Fungal; Saccharomyces cerevisiae - proteiny; biologická adaptace; Sequence Homology; homeostáza; Hydrogen-Ion Concentration